TARI OREK-OREK SEBAGAI IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL PADA SISWA SEKOLAH DASAR DI KABUPATEN NGAWI - Rizka Amalia (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2018)
Improving the quality of character education needs to be done in all aspects including through cultural contexts. This study aims to describe the implementation of character education based on local wisdom through Orek-Orek dance. The research approach used is descriptive qualitative research. His research sites are Paron Elementary School and Kedungputri 1 Elementary School, Ngawi District. Data collection techniques include study documentation, observation and interviews. Data analysis techniques include data reduction, data display, and conclusion drawing / verification. The results of the study show that the Orek-Orek dance still exists today because of the synergy and routine carried out in various events and learning in